2022
DOI: 10.1111/trf.17039
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell depletion in small‐volume bone marrow processing using manipulation with third‐party red blood cells: A comparison of the performance of the COBE spectra and the spectra Optia systems

Abstract: Background: For pediatric recipients, red blood cells (RBCs) are added to bone marrow (BM) collections before low RBC volume BM processing using COBE Spectra (COBE) or Spectra Optia (Optia). However, the processing efficiency of this approach has not been evaluated. This study aimed to evaluate RBC depletion and nucleated cell subpopulation recovery rates in third-party RBC-manipulated BM products processed with the COBE or Optia. Study Design and Methods: We retrospectively collected data on RBC depletion fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Unlike previous reports with LVL procedures, Hb or Hct was not significantly associated with CE2 for the target cells. 22,30,35,38,39 As our study did not include healthy donors and our previous experience suggested that maintaining a high Hct at leukapheresis contributed to improved CE2 for CD34 + , 35 we attempted to proactively increase Hct before leukapheresis by RBC transfusion in daily clinical setting. As a result, approximately 70% of patients in the LVL group received RBC transfusion for leukapheresis, leading to a possibility of underestimation of the relationship between CE2 for CD3 + cells and Hb or Hct.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Unlike previous reports with LVL procedures, Hb or Hct was not significantly associated with CE2 for the target cells. 22,30,35,38,39 As our study did not include healthy donors and our previous experience suggested that maintaining a high Hct at leukapheresis contributed to improved CE2 for CD34 + , 35 we attempted to proactively increase Hct before leukapheresis by RBC transfusion in daily clinical setting. As a result, approximately 70% of patients in the LVL group received RBC transfusion for leukapheresis, leading to a possibility of underestimation of the relationship between CE2 for CD3 + cells and Hb or Hct.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Following previous studies, LVL was defined as PBV ≥3-fold TBV, while normal-volume leukapheresis (NVL) was defined as PBV <3-fold TBV. [13][14][15][16][17][18][19][20][21][22]…”
Section: Apheresis Proceduresmentioning
confidence: 99%
See 2 more Smart Citations